Psychological stress and psychological support of Chinese nurses during severe public health events - Yufang Zhou; Youtian Wang; Meilian Huang; Chen Wang; Yuanxin Pan; Junrong Ye; Shengwei Wu; Chenxin Wu; Haoyun Wang; Ting Wang; Aixiang Xiao; Lin Yu (BMC Psychiatry, 2022)
Abstract The domestic health care system has been facing a difficult task, especially in medical care, and Chinese nurses are under tremendous psychological pressure. Psychological support is a protective factor to relieve stress. This study examined the stress level and characteristics of Chinese nurses with different psychological support-seeking behaviours. Data from online questionnaires for this cross-sectional study were collected between January 2020 and February 2020 and yielded 2248 valid questionnaires for analysis with a response rate of 99.8%. General information of the respondents was also collected. The nurses’ stress levels were assessed using the Perceived Stress Scale (PSS-10). T tests, chi-square tests, and linear regression were used to examine the relationships among the factors. The results of this survey showed that between January and February 2020, 26.9% of nurses received psychological counselling, and the proportion was higher among men and nurses with lower education. The PSS-10 was related to gender, age group, provincial severity, and confidence in the control of the epidemic. The results showed that psychological support can effectively improve the confidence of domestic nurses in the face of arduous work and effectively relieve the psychological pressure caused by a heavy workload.